Ceftolozane–tazobactam for the treatment of osteomyelitis caused by multidrug-resistant pathogens: a case series - Xing Tan (SAGE Publishing, 2019)
Ceftolozane–tazobactam (CT) is a recently approved novel cephalosporin and β-lactamase inhibitor combination agent with in vitro activity against various Gram-positive and Gram-negative pathogens, including several multidrug-resistant (MDR) Gram-negative organisms. CT is currently approved by the US Food and Drug Administration for the treatment of complicated intrabdominal infection and complicated urinary tract infection at a dose of 1.5 g intravenously every 8 h. This agent is an attractive option for MDR osteomyelitis (OM) treatment, but clinical data is limited to case reports and series. Here we report a series of five patients with MDR OM who were treated with CT. Pathogens involved in these infections were MDR Acinetobacter baumannii (two isolates) and MDR Pseudomonas aeruginosa (four isolates). Two patients were disease free 6 months after therapy was discontinued, one required an additional curative surgical procedure, and two (both on high-dose therapy) developed adverse reactions likely related to CT that necessitated early antibiotic discontinuation.